(untitled) (Journal of the College of Basic Education, 2026)
The Abbasids were deeply interested in the beauty of nature, utilizing its agricultural, water, and animal resources. People became enchanted by its breathtaking scenery, including the poet Abdullah ibn al-Mu‘tazz, who described it and poured his joys and sorrows into it. The poet embodied tears with various descriptions, focusing on their artistic and symbolic function as expressions of different emotions. In the context of the ruined campsite (ṭalal), he described tears as flowing, justified, confused, and weeping—giving them a sorrowful, negative connotation. In the theme of rainy nature, tears appeared in similes, likened to drops of dew, rain, and clouds in their pure, sparkling, and glistening form. Here, a new aesthetic vision emerged, linking human emotion to nature, with joy—not sorrow—as the source of tears, giving them a positive meaning. In cosmic nature (such as the night), he likened the night to a bereaved woman weeping in a moment of loss and pain—giving tears a tragic and deeply sorrowful connotation. The cooing of doves stirred Ibn al-Mu‘tazz’s emotions in the theme of living nature (animals: doves and turtledoves). The poet compared his own tears with those of the doves, finding his tears superficial in comparison to the heartfelt weeping of the bird. He shared his sorrow with the bird, joining it in mourning and lamentation. Thus, the meaning of tears here is emotional and sorrowful, symbolizing the poet’s loneliness and pain. In this way, tears became a symbol of the poet’s emotions.